The Power of Drosophila melanogaster for Modeling Neonicotinoid Effects on Pollinators and Identifying Novel Mechanisms - Tasman, Kiah; Rands, Sean A.; Hodge, James J. L. (Frontiers in Physiology, 2021)
Neonicotinoids are the most widely used insecticides in the world and are implicated in the widespread population declines of insects including pollinators. Neonicotinoids target nicotinic acetylcholine receptors which are expressed throughout the insect central nervous system, causing a wide range of sub-lethal effects on non-target insects. Here we review the potential of the fruit fly Drosophila melanogaster to model the sub-lethal effects of neonicotinoids on pollinators, by utilising its well-established assays that allow rapid identification and mechanistic characterisation of these effects. We compare studies on the effects of neonicotinoids on lethality, reproduction, locomotion, immunity, learning, circadian rhythms and sleep in D. melanogaster and a range of pollinators. We also highlight how the genetic tools available in D. melanogaster, such as GAL4/UAS targeted transgene expression system combined with RNAi lines to any gene in the genome including the different nicotinic acetylcholine receptor subunit genes, are set to elucidate the mechanisms that underlie the sub-lethal effects of these common pesticides. We argue that studying pollinators and D. melanogaster in tandem allows rapid elucidation of mechanisms of action, which translate well from D. melanogaster to pollinators. We focus on the recent identification of novel and important sublethal effects of neonicotinoids on circadian rhythms and sleep. The comparison of effects between D. melanogaster and pollinators and the use of genetic tools to identify mechanisms make a powerful partnership for the future discovery and testing of more specific insecticides.